2017
DOI: 10.1111/aogs.13248
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy before recurrent pregnancy loss more often complicated by post‐term birth and perinatal death

Abstract: Introduction. The cause of recurrent pregnancy loss often remains unknown. Possibly, pathophysiological pathways are shared with other pregnancy complications. Material and methods. All women with secondary recurrent pregnancy loss (SRPL) visiting Leiden University Medical Center (January 2000(January -2015 were included in this retrospective cohort to assess whether women with SRPL have a more complicated first pregnancy compared with control women. SRPL was defined as three or more consecutive pregnancy los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Four studies 11,26,35,38 investigated the association between a history of RSA and postpartum hemorrhage. The combined analysis result of the random‐effect model showed that there was no association between a history of RSA and postpartum hemorrhage ( I 2 = 89.3%, OR: 2.14, 95% CI: 0.94–4.88, p = 0.071).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies 11,26,35,38 investigated the association between a history of RSA and postpartum hemorrhage. The combined analysis result of the random‐effect model showed that there was no association between a history of RSA and postpartum hemorrhage ( I 2 = 89.3%, OR: 2.14, 95% CI: 0.94–4.88, p = 0.071).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 57 titles and abstracts were read based on the inclusion and exclusion criteria. Finally, 15 studies [10][11][12][13]26,[29][30][31][32][33][34][35][36][37][38] were included in this meta-analysis. The literature search flow chart is shown in Figure 1.…”
Section: Study Selections and Basic Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the risk of RM increases with successive pregnancy loss [10]. It has also been reported that risk factors for RM may be immunological, and may be associated with polycystic ovary apart from spontaneous abortions [11]. On the other hand, it has been reported that PCOS is a major factor responsible for high incidence of RM, and that the underlying causes of RM are genetic factors, as well as endocrine and autoimmune diseases [12].…”
Section: Discussionmentioning
confidence: 99%